Adopsi Prinsip Permanent Sovereignty Over Natural Resources (PSNR) Migas - Husna TR, Cut Asmaul (Jurnal Hukum & Pembangunan, 2016)
The specificity of the setting investment in upstream oil and gas consequences of role of the state that is large enough. This is because the upstream oil and gas sector requires capital investment costs are relatively large; high risk, the use of advanced technology and trained human resources. However, investment in upstream oil and gas sector also gives a great advantage. Therefore, oil and gas producing countries seek to maximize the full control over the affairs of operations, production, management, and marketing. It is supported by the United Nations General Assembly Resolution (UN) No. 2158 (XXI) of 25 November 1966 on Permanent Sovereignty over Natural Resources (PSNR) which called upon state oil producers to maximize the natural resources of oil and gas investments. Rooted in the right of self-determination and with the primary aim of enabling economic development for developing states, the principle of PSNR builds on prerogative sovereign of states. The Constitutional Court Decision No. 36/PUU-X/2012 and No. 002/PUU-I/2003 should be appreciated for correcting substance of Law Number 22 Year 2001